2019
DOI: 10.1038/s41598-019-43975-0
|View full text |Cite
|
Sign up to set email alerts
|

The Small GTPase Rac1 Increases Cell Surface Stiffness and Enhances 3D Migration Into Extracellular Matrices

Abstract: Membrane ruffling and lamellipodia formation promote the motility of adherent cells in two-dimensional motility assays by mechano-sensing of the microenvironment and initiation of focal adhesions towards their surroundings. Lamellipodium formation is stimulated by small Rho GTPases of the Rac subfamily, since genetic removal of these GTPases abolishes lamellipodium assembly. The relevance of lamellipodial or invadopodial structures for facilitating cellular mechanics and 3D cell motility is still unclear. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 91 publications
(143 reference statements)
2
54
0
Order By: Relevance
“…Here, we show that DEX transiently upregulated RhoA in hTM cells, and this transient increase was time-dependent, consistent with prior studies that reported increased cell contractility, and/or fibrotic changes in hTM cells 49,51,65 and non-ocular tissues. 50 Although there was significant interaction between treatment and time for the expression of Rac 1/2/3 in hTM cells, no marked differences were observed between Veh and DEX. This finding may probably suggest DEX-induced fibrotic phenotypes in hTM cells is independent of Rac 1, 33 which may be dormant in hTM cells.…”
Section: Dex and Gim Temporally And Differentially Modulate Specific mentioning
confidence: 85%
See 3 more Smart Citations
“…Here, we show that DEX transiently upregulated RhoA in hTM cells, and this transient increase was time-dependent, consistent with prior studies that reported increased cell contractility, and/or fibrotic changes in hTM cells 49,51,65 and non-ocular tissues. 50 Although there was significant interaction between treatment and time for the expression of Rac 1/2/3 in hTM cells, no marked differences were observed between Veh and DEX. This finding may probably suggest DEX-induced fibrotic phenotypes in hTM cells is independent of Rac 1, 33 which may be dormant in hTM cells.…”
Section: Dex and Gim Temporally And Differentially Modulate Specific mentioning
confidence: 85%
“…We recently documented crosslinked CDM stiffens hTM cells 81 and our group has previously reported DEX increases stiffness of hTM cells 7 ; herein, we document that GIM-mediated increased cell stiffening is consistent across multiple time points. Several studies have implicated substratum stiffness, 118 integrins, 73 caveolins, 119 and Rho GTPases 50,[120][121][122] in altered biomechanics in ocular and non-ocular cells / tissues. Therefore, the time-independent increase in stiffness of cells cultured on GIMs may be due in part to the integration of FN ED-A / FN ED-B overexpression, specific integrins, caveolins and Rho GTPases in hTM cells or aberrant TGFβ2 signaling.…”
Section: Gim Sustain Stiffening Of Htm Cells Across All Time Pointsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the hypothesis is that mechanical stimulation decreases the expression of integrin β3, which in turn decreases the activation of Rac1. In opposition to other investigations, in which Rac1 expression strengthened the migration and invasion of cells (Kunschmann et al, 2019). It is hypothesized that various types of force use distinct signal transduction pathways, in which the force is primarily modulated by the interaction of cells with various ligands.…”
Section: Interaction Between Transient Strain and Expression Of Proteinsmentioning
confidence: 80%